2021
DOI: 10.3390/diagnostics11020231
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Amyotrophic Lateral Sclerosis: Up to Date

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by gradual loss of upper and lower motor neurons and their pathways, usually without affecting the extraocular and sphincter muscles. The cause of the disease is not yet known. It is a chain of subsequent events, ending in programmed cell death in selective neuronal subpopulations. The prognosis for survival is rather short with a median of 2 to 4 years. Survival may be prolonged based on prompt diagnosis, ALS subtype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 99 publications
(67 reference statements)
0
21
0
2
Order By: Relevance
“…The abnormal rate of EMG in ALS cases was as high as 85%. EMG remains a basic method to determine the loss of motor units, which include anterior horn cell, motor nerve, neuromuscular junction, and the muscle fibers [ 8 ]. In the process of EMG detection, it was found that in patients with early ALS, EMG mostly showed extensive neurogenic damage at three or more sites, so EMG was an important tool to assist in the diagnosis of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal rate of EMG in ALS cases was as high as 85%. EMG remains a basic method to determine the loss of motor units, which include anterior horn cell, motor nerve, neuromuscular junction, and the muscle fibers [ 8 ]. In the process of EMG detection, it was found that in patients with early ALS, EMG mostly showed extensive neurogenic damage at three or more sites, so EMG was an important tool to assist in the diagnosis of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…This, along with the complete absence of G93A and D90A mutations of SOD1 in the patients, is an unexpected and relevant finding about amyotrophic lateral sclerosis genetics, its physiopathology and other neurodegenerative conditions. It is therefore necessary to confirm whether this genotype of 8 repeats in C9orf72 is pathologic in our population and to determine its importance as a diagnostic biomarker or as a risk factor for amyotrophic lateral sclerosis, as it is currently being done in other populations (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The other possibilities were ruled out based on the history and clinical examination. He was then diagnosed ALS on the basis of Gold Coast criteria [ [5] , [6] , [7] ]. On exome sequencing [ 8 ], an atypical gene was isolated from gene sequencing as shown in Table 1 .…”
Section: Case Presentationmentioning
confidence: 99%